APPLICATION OF CHEST AND INFRA RED PHYSIOTHERAPY ON BREATHWAY CLEANING IN TODDLER AGE 0-24 MONTHS WITH COMMON COLD - Lestari, Tri Endah Widi; Fitriyani, Tanti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
Coughs and colds are upper respiratory tract infections (ARI) which often occur in children under 5 years and can occur 6-9 times a year. Symptoms of a cold cough are excessive mucus production which makes it difficult for children to breathe because toddlers cannot produce their own secretions so it can cause breathing problems andfeel restless so need to be given chest physiotherapy and infrared intervention. The aim of this research is to find outeffectivenessfrom the application of physiotherapy and infrared to clear the airway in toddlers 0-24 months with coughs and colds. This research methodusedescriptive method with a case study approach with research subjects of 5 toddler respondents aged 0-24 months with inclusion criteria. The instruments used include observation sheets and Borg score assessments. The results of this study were that it was able to overcome airway clearance in the respondent's condition after being given intervention twice a day with a duration of 50 minutes for 3 days with sputum output of (60%) and no sputum output of (40%), a decrease in frequency.Respiratory, decreased Borg score, no shortness of breath and baby sleeps more soundly.Conclusion: the application of chest physiotherapy and infrared is effective in overcoming airway clearance problems in toddlers aged 0-24 months with coughs and colds.